2008
DOI: 10.1016/j.jcf.2007.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasound and biopsy findings in children with cystic fibrosis related liver disease

Abstract: The diagnosis of early liver disease in cystic fibrosis cannot reliably be made on the basis of ultrasound alone. A normal ultrasound does not preclude significant liver fibrosis in cystic fibrosis. An abnormal US that suggests cirrhosis predicts the presence of moderate to severe liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 29 publications
2
42
0
1
Order By: Relevance
“…However, our practice is to perform annual ultrasound of the abdomen in all patients with CF, as ultrasound is non-invasive, cost-effective and highly valuable for the diagnosis of hepatic steatosis, cirrhosis and complications of portal hypertension such as ascites and splenomegaly. Yet, ultrasound cannot reliably exclude early liver disease [9] and disparity between results of ultrasound and liver enzymes was observed in up to 24% of CF patients [10,11]. Several studies have demonstrated that clinical evaluation, serum liver enzymes and ultrasound are imprecise for detecting the presence and predicting the progression of liver disease [10,11,12,13].…”
Section: Diagnosis Of Cfldmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our practice is to perform annual ultrasound of the abdomen in all patients with CF, as ultrasound is non-invasive, cost-effective and highly valuable for the diagnosis of hepatic steatosis, cirrhosis and complications of portal hypertension such as ascites and splenomegaly. Yet, ultrasound cannot reliably exclude early liver disease [9] and disparity between results of ultrasound and liver enzymes was observed in up to 24% of CF patients [10,11]. Several studies have demonstrated that clinical evaluation, serum liver enzymes and ultrasound are imprecise for detecting the presence and predicting the progression of liver disease [10,11,12,13].…”
Section: Diagnosis Of Cfldmentioning
confidence: 99%
“…Thus, for patients in whom diagnosis is still inconclusive after standard work-up (see above) including exclusion of other causes of liver disease (viral, autoimmune, metabolic, genetic) percutaneous liver biopsy representing the diagnostic gold standard, can be performed [8]. Although liver biopsy is invasive, complication rates after liver biopsy in CF patients seem to be low even when dual pass liver biopsies are performed (no bleeding, hospital admission, prolonged pain or surgery [9,13]. However, a substantial sampling error due to typically focally distributed lesions in CFLD can complicate diagnostic algorithms.…”
Section: Diagnosis Of Cfldmentioning
confidence: 99%
“…However, in many studies these diagnostic criteria were modified resulting in heterogeneous data of CFLD prevalence [1]. The focal pattern of liver involvement results in disaccordance between clinical findings and histological staging and a high proportion of sampling errors [8]. Therefore, although liver biopsy may help to identify patients at risk for development of clinically significant liver disease [9] it is not a standard procedure in CF [1].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional ultrasound examination with B-mode seems to be insufficient in assessing liver condition in patients with CF [22]. Research conducted by Behrens et al and Menten et al compares respectively ARFI and TE value to B-mode.…”
Section: Cf-associated Liver Diseasementioning
confidence: 99%